Phospholipase A2 isoforms are altered in chronic pancreatitis. - Kashiwagi, M (1998)
OBJECTIVE: To determine if phospholipase A2 (PLA2) type II and type IV mRNA expression and protein are altered in chronic pancreatitis. SUMMARY BACKGROUND DATA: PLA2s have an important regulatory function in several signaling pathways, especially in inflammation. In this study, we examined the expression of three PLA2 isoforms (type I, type II, and type IV) in chronic pancreatitis. METHODS: The distribution of PLA2 was studied in 15 pancreas samples obtained from patients with chronic pancreatitis using immunohistochemical, Northern blot, and in situ hybridization techniques. Normal pancreas obtained from healthy organ donors served as control. RESULTS: Northern blot analysis revealed enhanced mRNA levels of PLA2 type II (5.7-fold) and type IV (5.1-fold) in chronic pancreatitis (p < 0.01) versus normal pancreas. In normal pancreas, intense PLA2 type I immunostaining was present in acinar cells, whereas PLA2 type II immunostaining was visible only in some acinar cells. In chronic pancreatitis, PLA2 type II immunostaining was present more frequently and with higher intensity in acinar cells. Furthermore, PLA2 type II immunoreactivity was more abundant in metaplastic ductal cells in the chronic pancreatitis samples. By in situ hybridization, areas with ductal metaplasia in chronic pancreatitis exhibited intense PLA2 type IV mRNA signals. All chronic pancreatitis tissues with concomitantly increased mRNA expression for PLA2 type II and type IV exhibited a higher degree of degeneration, ductal metaplasia, and fibrosis. CONCLUSIONS: Upregulation of PLA2 types II and IV in areas with more histologic damage suggests that these PLA2 isoforms might contribute to the morphologic changes that occur in chronic pancreatitis.